English Language Proficiency and Curriculum Development for Air Traffic Control (Journal of Human Sciences, 2025)
The aim of this study was to investigate the needs of students in the Air-Traffic Control department. Participants of the study were 30 students in the final semester at the Technical College of Civil Aviation and Meteorology Libya, (TCCAM). The information of the students’ needs was obtained through a descriptive questionnaire consisting of the students current & target needs known as necessities, wants and lacks. The questionnaire results highlighted the most critical English skills needed: speaking and listening. Additionally, the findings identified several important topics -referred to as necessities- that should be included in the syllabus. However, the results manifested some gaps (lacks) between the English topics that should be learnt with the topics that the students had already learnt. Additionally, the students expressed specific preferences regarding the English learning process.  The findings, also, revealed the degree of importance of language skills which were necessary for the students future career and indicated their strong needs to improve those skills as a result of the learning styles and the teaching materials used. Moreover, the findings demonstrated a strong willingness among students to improve their speaking and listening skills in English and that the students' dissatisfaction with their teachers, teaching methods, learning styles and input length was clearly identified. Therefore, results of this study will hopefully be essential for the ESP practitioners, aviation English teachers and teaching material designers to improve the quality of the ESP syllabus, more specifically, the aviation syllabus.